Factors Affecting the New Public Management of Local Administrative Organization, Ban Phaeng District, Nakhon Phanom Province - Wongmakvaree, Pachara; Thongrueang, Khemika; Inthanon, Worawut (Interdisciplinary Academic and Research Journal, 2023)
New Public Management is one of the concepts that the public sector has changed from the traditional administration to apply the concept of administrative administration to apply to various policies made by local government organizations for the people. This is to create participation of all sectors in the local area to solve problems effectively and increase the potential and capacity of the local community. Thus, this research aims; (1) to study the level of new public management factors of local administrative organizations. (2) To study the transformational leadership affecting the new public management of local administrative organizations. (3) To study the transformational leadership affecting the new public management of local government organizations. This research was quantitative and held in Ban Phaeng District, Nakhon Phanom Province. The sample group was a total of 196 local administrative personnel in Ban Phaeng District, Nakhon Phanom Province were obtained by purposive selection. The tool used to collect data was a questionnaire. Statistics used to analyze the data were frequency, percentage, mean, standard deviation, Pearson's correlation coefficient, and multiple linear regression analysis. The results showed that (1) the factors of new public management of local administrative organizations overall were at the highest level. (2) The new public management of local administrative organizations classified by personal factors including job positions, and monthly incomes were significantly different at the.05 level. (3) Factors affecting the new public management of local administrative organizations were statistically significant at the.05 level, sorted from the variables that affected the variation in the dependent variables of standardized form from highest to lowest as follows: Ideological influence factor (X1 Beta=.268), Motivation factor (X3 Beta=.261), Individuality factor (X4 Beta= -.307).